PENGARUH MEDIA KONKRET TERHADAP HASIL BELAJAR SISWA PADA MATERI BANGUN RUANG DI KELAS II SD - Sabila Haqiqi; Novia Rahma Rista Utami; Dita Primashanti Koesmadi (STKIP Subang, 2025)
This study aims to determine the effectiveness of using concrete media to improvestudent learning outcomes in the topic of three-dimensional shapes amongsecond-grade students at SDN Bangunrejo Lor 1, Pitu District. This researchemployed a quantitative approach using a pre-experimental design of the OneGroup Pretest-Posttest type. Data were collected through multiple-choice testsadministered before and after the treatment. Data analysis was carried out usingSPSS version 26, applying the Kolmogorov-Smirnov normality test and the pairedsample t-test for hypothesis testing. The results showed a significance value (2-tailed) of 0.000 < 0.05 and a t-count of 11.856 > t-table value of 2.045, indicating asignificant difference between pretest and posttest scores. These findings suggestthat the use of concrete media effectively enhances students’ understanding andlearning outcomes. Observations in the classroom revealed that many studentsencountered difficulties in grasping the abstract concepts of three-dimensionalshapes due to the dominance of teacher-centered learning and the lack ofengaging instructional media. The use of concrete media, such as three-dimensional teaching aids, provides visual and tangible representations ofgeometric concepts, making it easier for students to comprehend the material. Inaddition, this approach fosters greater student engagement, motivation, and activeparticipation in the learning process. Therefore, it is recommended that concretemedia be incorporated into mathematics instruction to create a more interactiveand meaningful learning environment.